Quality of Health Social Security Agency Services at Tugu Public Health Center - Muhamad Tegar Purna Bhakti; Gotfridus Goris Seran; Neng Apriliyani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The importance of healthcare services in community development is to increase individual productivity. The health center serves patients in its area, which includes Cimanggis District, Depok City. It will be difficult to provide effective and efficient healthcare services because the population of Cimanggis District will increase to 251,002 by 2024. Studies show that, especially at the Tugu Community Health Center, there is a difference between what the community expects from the services and what happens. Developed the Service Quality Dimensions (SERVAQUAL) model, which assesses service quality using the TERRA dimensions. This researcher used a descriptive quantitative approach with data collection techniques including questionnaires, observations, and interviews. The results show that the Tugu Community Health Center received an average score of 2.7 from the TERRA dimension, which means